The Effect of Local Microorganisms, Pseudomonas flourescens and Rhizobium sp. on the Growth of Soybean in Calcareous Soil - A’yun, Lutpita Amiliya; Rahayu, Yuni Sri; Dewi, Sari Kusuma (LenteraBio : Berkala Ilmiah Biologi, 2022)
One of the efforts to improve N and P nutrient deficiency in calcareous soil and the high unmet demand for soybeans in Indonesia is using spoiled rice MOL, P. flourescens, and Rhizobium sp. This study aimed to determine the effect of giving spoiled rice MOL, P. flourescens, and Rhizobium sp. on soybean growth and determine the best treatment for soybean growth on calcareous soil. This experimental study used a randomized block design with seven treatments and three replications included: control, MOL, P. flourescens, Rhizobium sp., MOL+P. flourescens, MOL+Rhizobium sp., and MOL+P. flourescens+Rhizobium sp. Parameters included are level of N P, number of root nodules, root nodule biomass, number of active root nodules, plant height, root length, number of leaves, wet biomass, and number of flowers. Data were analyzed descriptively quantitatively using one-way ANOVA followed by Duncan’s test. The results showed that the combination of spoiled rice MOL, P. flourescens, and Rhizobium sp. significant effect on soybean growth in calcareous soil. Spoiled rice MOL and Rhizobium sp. has the best result on the leaf amount, amount of root nodules, and amount of active root nodules. A combination of spoiled rice MOL, P. flourescens, and Rhizobium sp. has the best result on N level, P level, root nodule biomass, plant height, root length, wet biomass, and flowers amount of soybean in calcareous soil.